2018
DOI: 10.5897/ijfa2018.0682
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of the fish meal by the earthworm and maggot meal in the feed of Nile tilapia Oreochromis niloticus reared in freshwater

Abstract: The present experiment was conducted to evaluate the efficacy of dietary protein from maggot meal and earthworm meal to replace fish meal protein in Oreochromis niloticus juvenile feed. The fish used for this experiment come from the experience of the larval phase during which fish were fed with the formulated diets [fish diet (FD), maggot diet (MD) and earthworm diet (ED)] content 40% crude protein and the commercial diet (CD) content 34.5% crude protein. At the end of this larval phase, the average weights w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Combined with the rising price of fish meal and limited fishery resources, it is necessary to search for alternative protein sources applied in aquafeeds ( Natale et al, 2013 ). Recently, the research on alternative protein sources mainly focused on vegetable protein and their fermentation treatment ( Dossou et al, 2018 ; Ismail et al, 2020 ; Iqbal et al, 2021 ; Rahimnejad et al, 2021 ) as well as animal protein ( Moutinho et al, 2017 ; Medard et al, 2018 ; Sabbagh et al, 2019 ; Tazikeh et al, 2020 ) for their lower price. However, the defects of poor palatability, low digestibility and imbalanced amino acids profile limit their further application in aquafeeds.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the rising price of fish meal and limited fishery resources, it is necessary to search for alternative protein sources applied in aquafeeds ( Natale et al, 2013 ). Recently, the research on alternative protein sources mainly focused on vegetable protein and their fermentation treatment ( Dossou et al, 2018 ; Ismail et al, 2020 ; Iqbal et al, 2021 ; Rahimnejad et al, 2021 ) as well as animal protein ( Moutinho et al, 2017 ; Medard et al, 2018 ; Sabbagh et al, 2019 ; Tazikeh et al, 2020 ) for their lower price. However, the defects of poor palatability, low digestibility and imbalanced amino acids profile limit their further application in aquafeeds.…”
Section: Introductionmentioning
confidence: 99%
“…The fly (L. sericata) maggot was considered one of the important animal that can be grown in the chicken manure medium (Ali Khan et al, 2012;Hwangbo et al, 2009). Studies have shown that maggot meal may be a very effective replacement for fish meal, which serves as an excellent source of protein for making fish feed for commercial or small-scale aquaculture (Jahan et al, 2020;Medard et al, 2018;Djissou et al, 2016;Aniebo et al, 2009). Different animal and fish species were used in experiments to determine the impact of using maggot meal instead of other types of protein (Xu et al, 2022;Khan et al, 2016;Makinde and John, 2015;Aniebo et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that reducing farming costs is one of the main strategies to improve farming economic efficiency [ 4 ]. In modern aquaculture, feed costs usually account for more than 50% of total costs, since fish meal is increasingly expensive [ 5 , 6 , 7 ]. Currently, fish meal remains an integral part of commercial feed for striped catfish, remaining at 20–60% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%